A highly variable methanol maser in G111.256–0.770. Issue 1 (14th February 2019) - Durjasz, M; Szymczak, M; Olech, M
Abstract: G111.256−0.770 is a high-mass young stellar object associated with a weak 6.7 GHz methanol maser showing strong variability. We present results of a multi-epoch monitoring program of the target, conducted with the Torun 32 m telescope for more than a decade. We found that the isotropic maser luminosity varied by a factor 16 on a time-scale of 5–6 yr and individual features showed small amplitude short-lived (∼0.2 yr) bursts superimposed on higher amplitude slow (>5 yr) variations. The maser integrated flux density appears to be correlated with the near-infrared flux observed with the (NEO)WISE, supporting radiative pumping of the maser line.